Optimization of Anesthetic Provision During Operations on the Foot - D. S. Yasnev; A. V. Zabusov; S. V. Larionov; P. A. Lyubashevsky; P. S. Zhbannikov (Общая реаниматология)
Trauma of foot and an ankle have high prevalence among the population. Anesthesiological maintenance of operative treatment of such traumas represents a separate problem because of high durations of operation, expressiveness of a postoperative painful syndrome. The important feature of a heavy trauma of the foot is infringement regional haemocirculation of development of a vascular spasm. We offer a technique complex of perioperative analgesia, based on a combination of spinal anesthesia and parenteral introductions of synthetic analogue L-encephaline (Dalargin). Intraoperative dalargin was entered intravenously, in postoperative period — intramuscularly in a combination with ketorol. It is surveyed 42 patients. In comparison with the control, got prolongation of effective spinal anesthesia, decrease of intensity of a postoperative painful syndrome that marked according to a visual analog scale, increase of thresholds of painful sensitivity by the data of electrosensometriya, improvement regional haemocirculation and microcirculation be the date of ultrasonic dopplero-graphia and electrothermometry of a stops skin. Stress — limiting action of a preparation was showed including reduction in comparison with the control leucocitosis and neutrophil shift of leucocitar formulas in the postoperative period, absence of episodes hiperglicemiya. Offered method permits raise of duration of the analgetick effect of spinal anaesthesia, evade appointment in postoperative period opioid analgeticks, improve results of surgical treatment at the expense of normalization of the regional haemodinamicks and avert isemiya of local tissue.